2013
DOI: 10.1111/jch.12116
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Pregnancy Is a Risk Factor for Microalbuminuria Later in Life

Abstract: We aimed to compare renal function, by estimated GFR, and albuminuria, in three groups of women: nulliparous women, women with a history of normotensive pregnancies, and women with a history of at least one hypertensive pregnancy. Women who participated in the second Family Blood Pressure Program Study visit (2000–2004) and had serum creatinine and urine albumin measurements (n=3015) were categorized as having had no pregnancy lasting greater than 6 months (n=341), having had only normotensive pregnancies (n=2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 40 publications
(89 reference statements)
1
22
0
4
Order By: Relevance
“…(26) Although this injury is thought to be transient,(27) some evidence suggests that moderately increased albuminuria is present for up to 20 years after the hypertensive pregnancy. (2830) Podocyturia may be sustained in the post-partum period in some women with preeclampsia, which could reflect ongoing kidney damage or even systemic endothelial dysfunction. (31, 32) Third, women with preeclampsia are at increased risk of hypertension, and may develop hypertension earlier than women with normotensive pregnancies, suggesting that hypertension may be an important mediating factor on the causal pathway from preeclampsia to ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…(26) Although this injury is thought to be transient,(27) some evidence suggests that moderately increased albuminuria is present for up to 20 years after the hypertensive pregnancy. (2830) Podocyturia may be sustained in the post-partum period in some women with preeclampsia, which could reflect ongoing kidney damage or even systemic endothelial dysfunction. (31, 32) Third, women with preeclampsia are at increased risk of hypertension, and may develop hypertension earlier than women with normotensive pregnancies, suggesting that hypertension may be an important mediating factor on the causal pathway from preeclampsia to ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies support that women with a history of pre-eclampsia have an increased future risk of albuminuria, chronic kidney disease (CKD), and end stage renal disease (ESRD). 104108 It is unclear whether this association is independent of risk factors that may be common to pre-eclampsia and renal disease (Figure 3). In a mouse model of selective podocyte depletion using diphtheria toxin, 109 a single episode of podocyte injury resulted in glomerular destabilization and persistent podocyte loss.…”
Section: Pre-eclampsia Podocyte Injury and Future Chronic Renal Dismentioning
confidence: 99%
“…Baseline urine albumin excretion was significantly associated with the risk for developing hypertension (Odds ratio 2.29; 95% confidence interval 1.77 to 2.95 per 10-fold increase of urine albumin excretion). Kattah AG et al (2013) In this study, we present evidence that women with a history of hypertension in pregnancy are at significantly increased risk for microalbuminuria later in life as compared to those with normotensive pregnancies.…”
Section: Observations In Microalbuminuria Tested Patients At 18-22 Wementioning
confidence: 56%
“…It may be concluded that early pregnancy levels of microalbuminuria can be used as predictors of pre-eclampsia with high negative predictive value. (9,10) Out of 200 Subjects included at 18-22 Weeks  186 women could be investigated by 23-28 weeks.  2 women aborted.…”
Section: Resultsmentioning
confidence: 99%